2021
DOI: 10.14309/ajg.0000000000001266
|View full text |Cite
|
Sign up to set email alerts
|

Antispasmodics for Chronic Abdominal Pain: Analysis of North American Treatment Options

Abstract: Chronic abdominal pain is a common gastrointestinal (GI) symptom that characterizes many functional GI disorders/disorders of gut-brain interaction, including irritable bowel syndrome, functional dyspepsia, and centrally mediated abdominal pain syndrome. The symptoms of abdominal pain in these highly prevalent disorders are often treated with antispasmodic agents. Antispasmodic treatment includes a broad range of therapeutic classes with different mechanisms of action, including anticholinergic/antimuscarinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 55 publications
0
12
0
2
Order By: Relevance
“…Some may also help with vomiting and nausea. Jackson et al 101 Kaplan and Carson 102 Khoury et al 103 Brzozowska et al 104 Anemüller et al 105 Corticosteroid Prednisone and methylprednisolone Used via oral or intravenous for more severe cases of allergic reaction (controls urticaria, angioedema and pruritis) Ghahramani and Temprano 106 Wen et al 107 Mast cell stabilizer Oral cromolyn solution Reduces persistent gastrointestinal symptoms when avoidance diet is insufficient Commins 42 Antiemetic Domperidone and metoclopramide Reduces vomiting and nausea Zhang et al 108 Saleem and Nilsson 109 Antispasmodic Dicycloverine and hyoscine Helps controlling abdominal pain Guillier et al 110 Brzozowska et al 104 Brenner and Lacy 111 Antidiarrheal Loperamide Used to stop or slow diarrhea (anti-motility drug) Kaplan and Carson 102 Bircher et al 112 Laxative Sennosides and bisacodyl Treat constipation by stimulating bowel movement Emmanuel et al 113 Saleem and Nilsson 109 …”
Section: Treatment/management Methodsmentioning
confidence: 99%
“…Some may also help with vomiting and nausea. Jackson et al 101 Kaplan and Carson 102 Khoury et al 103 Brzozowska et al 104 Anemüller et al 105 Corticosteroid Prednisone and methylprednisolone Used via oral or intravenous for more severe cases of allergic reaction (controls urticaria, angioedema and pruritis) Ghahramani and Temprano 106 Wen et al 107 Mast cell stabilizer Oral cromolyn solution Reduces persistent gastrointestinal symptoms when avoidance diet is insufficient Commins 42 Antiemetic Domperidone and metoclopramide Reduces vomiting and nausea Zhang et al 108 Saleem and Nilsson 109 Antispasmodic Dicycloverine and hyoscine Helps controlling abdominal pain Guillier et al 110 Brzozowska et al 104 Brenner and Lacy 111 Antidiarrheal Loperamide Used to stop or slow diarrhea (anti-motility drug) Kaplan and Carson 102 Bircher et al 112 Laxative Sennosides and bisacodyl Treat constipation by stimulating bowel movement Emmanuel et al 113 Saleem and Nilsson 109 …”
Section: Treatment/management Methodsmentioning
confidence: 99%
“…Tienen efectos extraintestinales, y posibles efectos colaterales como boca seca, taquicardia, visión borrosa (125,126).…”
Section: Otros Antiespasmódicosunclassified
“…Este síntoma no hace parte de los criterios de Roma IV para el diagnóstico de SII, sin embargo, la mayoría de los pacientes lo presentan y su severidad se correlaciona con menor calidad de vida (121,122). Los medicamentos que han demostrado eficacia en la resolución del Bloating son: Rifaximina, Eluxadolina, Bromuro de pinaverio, de otilonio (58,(126)(127)(128)(129)(130)(131)(132)(133)(155)(156). Los pacientes con este síntoma, presentan con mayor frecuencia alteración de la microbiota y esto ha estimulado explorar la posibilidad de trasplante fecal, en casos severos (193,194).…”
Section: Otras Opcionesunclassified
“…Multiple meta-analyses and randomized controlled trials have shown that antispasmodic drugs are more efficacious than placebo at improving abdominal pain in patients with IBS. [43][44][45][46][47][48] However, because of the lack of head-to-head trials and sparsity of recent data, limited evidence exists to support differentiation of antispasmodic therapies. There are also very few studies, which have specifically investigated antispasmodics as a treatment for FACP.…”
Section: Commentsmentioning
confidence: 99%